Steps to be followed when home currency is weak - KUMAR, DR. P. PRAVEEN; NAAZ, MS. S. MAQSOODA (The journal of contemporary issues in business and government, 2020)
The study of the research paper deals with the money market and the appreciation of home currency value. The exchange rate mainly depends on the value of the home currency and the investments made by the people in the country. Investment plays a major role in currency appreciation. Trading with more than one currency at global level is called as Foreign Exchange. The Forex market deals with the currency exchange at global level. The value of home currency depends on the rate of exchange. The exchanging rate of currency can affect the trading factors of the country. Even the currency value can be determined by the import export of the country. Inflation plays a vital role in the Forex market. The inflation is expected to have a pessimistic impact on the exchange rate, low inflation does not assure favorable exchange during high inflation rate has a negative impact. Investments made by people of the country helps to avoid inflation.